Low coverage rate and awareness of influenza vaccine among older people in Shanghai, China: A cross-sectional study - Chuchu Ye; Weiping Zhu; Jianxing Yu; Zhongjie Li; Wenbiao Hu; Lipeng Hao; Yuanping Wang; Hongmei Xu; Qiao Sun; Genming Zhao (Taylor & Francis Group, 2018)
Background: Older individuals are at high risk for morbidity and mortality due to influenza, and the most effective way to prevent influenza is yearly vaccination. In China, the influenza vaccine is not covered by the national Expanded Program on Immunization, and more evidence is needed about influenza vaccine usage among older individuals. Objective: To determine the influenza vaccination coverage and its influencing factors, and understand barriers to older adults receiving influenza vaccinations in Shanghai, China. Methods: A cross-sectional survey was conducted with residents aged 60 and older. Vaccination status in the 2016-17 influenza season and reasons for or against vaccination were surveyed. The vaccination coverage rates were adjusted by gender, age and community distribution, and potential factors influencing vaccination uptake were determined by bivariate logistic regression. Results: In total, 253 of the 4417 respondents received an influenza vaccine during the 2016-17 season, yielding an adjusted coverage rate of 5.2% (95% CI, 4.5-5.8). The frequency of receiving the vaccine was higher for older individuals living with family/friends than that for those living alone (p < 0.05), and lower among individuals with chronic respiratory diseases (p < 0.05). Among unvaccinated respondents, lack of influenza vaccine awareness was the most common reason for being unvaccinated (48.3%, 2012/4164). Conclusion: Influenza vaccination coverage is extremely low among older people in Shanghai, and lack of awareness of the influenza vaccine might be a potential barrier to vaccination. Our study highlights the need for an appropriate influenza vaccination strategy and program targeting the older population.